A novel two-stage anoxic/oxic-moving bed biofilm reactor process for biological nitrogen removal in a full-scale municipal WWTP: Performance and bacterial community analysis. (December 2022) - Zhou, Xiaolin; Zhang, Yuan; Li, Zihao; Sun, Pengcheng; Hui, Xiaoliang; Fan, Xing; Bi, Xuejun; Yang, Tang; Huang, Shujuan; Cheng, Lihua; Ratnaweera, Harsha
Abstract: The application of a novel two-stage anoxic/oxic-moving bed biofilm reactor (TS-A/O-MBBR) was validated in a full-scale municipal wastewater treatment plant (WWTP), and its working mechanism was analysed for biological nitrogen removal in this study. Over one year, at a hydraulic residence time of only 9.8 h, the effluent chemical oxygen demand, ammonia nitrogen and total nitrogen (TN) concentrations remained below 40, 2 and 15 mg/L, which met strict emission standards. The seven compartments in this unit performed different functions, and together accomplished organics and nitrogen removal. TN removal could be controlled by the external carbon sources dosage added to the postanoxic compartments to cost effectively meet the standard with the lowest cost. The maximum TN removal efficiency and minimum effluent TN concentration reached 91.76 % and 4.12 mg/L, respectively. The bacterial communities differed in the suspended solids and preoxic, postanoxic and oxic biofilms ( r  = 0.87 and P  = 0.001). The top 30 most abundant identified bacterial genera in biofilms included 24 denitrifying genera and 2 nitrifying genera. The most abundant biofilm genus was Methylotenera, which played important roles in denitrification in the anoxic compartments. 1 and 24 denitrifying genera were only abundant in the postanoxic and preanoxic compartments, respectively. Nitrosomonas and Nitrospira were abundant in the oxic compartments, and played roles in nitrification. This study verified the feasibility of the TS-A/O-MBBR process in a full-scale WWTP, and investigated its working mechanism. Graphical abstract: Unlabelled Image Highlights: Novel two-stage A/O-MBBR were applied in full-scale WWTP. Average COD and NH4 + -N removal efficiencies were 91.68 % and 99.11 %, respectively. Minimum effluent TN was 4.12 mg/ L, and maximum TN efficiency was 91.76 %. Different bacterial communities were in SS and three groups of biofilms. 26 of top 30 abundant genera in biofilms were denitrifying and nitrifying bacteria.